2022
DOI: 10.1039/d2ta04011e
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage electrolysis of H2O and CO2 to methanol: CO2-to-methane reduction at the cathode and subsequent methane-to-methanol oxidation at the anode

Abstract: Co-electrolysis of H2O and N/C sources to valuable chemicals has the potential to contribute to global warming mitigation. We here report the electrochemical conversion of H2O and CO2 into methanol...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Our previous XPS study of the Pt anode after DC electrolysis of humidified methane indicated that the Pt was oxidized to high-valence states (i.e., PtO, PtO x , and PtO 2 ) (Figure a) . By contrast, compared with the deconvoluted spectra after DC electrolysis of humidified methane, those after DC electrolysis of unhumidified methane showed lower intensities of double peaks indexed to PtO and PtO x and the disappearance of the PtO 2 peak (Figure b).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Our previous XPS study of the Pt anode after DC electrolysis of humidified methane indicated that the Pt was oxidized to high-valence states (i.e., PtO, PtO x , and PtO 2 ) (Figure a) . By contrast, compared with the deconvoluted spectra after DC electrolysis of humidified methane, those after DC electrolysis of unhumidified methane showed lower intensities of double peaks indexed to PtO and PtO x and the disappearance of the PtO 2 peak (Figure b).…”
Section: Resultsmentioning
confidence: 90%
“…The Sn 0.9 In 0.1 P 2 O 7 powder was synthesized using a previously reported method. 20 Sn 0.9 In 0.1 P 2 O 7 powder (1 g) was mixed with 0.04 g of PTFE powder using a mortar and pestle, and the resultant mixture was cold-rolled to a thickness of 200 μm using a laboratory rolling mill. Anodes were prepared by depositing Pt particles onto the surface of the electrolyte by sputtering (Sanyu Electron, SC-701MkII) under an Ar atmosphere (Figure S1).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, our DFT calculations on CoOOH show that for a potential below ∼1 V, desorption of methanol coupled with adsorption of OH – on the Co site is thermodynamically favored vs further oxidation to methoxy, so that electrocatalytic oxidation with the control of the potential could open a possibility of selective formation of methanol. Moving to the gas phase, humidified membrane electrode assemblies could be a viable approach to electrochemical methane to methanol transformation systems, provided the four conditions above of high methane transport, high metal oxide catalyst conductivity, fast methanol desorption relative to overoxidation, and fast methanol product collection are met. …”
Section: Discussionmentioning
confidence: 99%